Can the Growth of Mega-Journals Affect Authors' Choice of Journal?. Issue 2 (3rd April 2017) - Shin, Eun-Ja
ABSTRACT: The growth of mega-journals has also brought about changes in authorship. This study uses collected data to identify the transitions of mega-journal publishing and changes of authorship. For authors interested in publishing in mega-journals, the publication of South Korean authors in these mega-journals is specifically sampled and checked, revealing that mega-journals are increasingly the targets for publication. Some mega-journals have an impact factor even if they have only been publishing for 5–10 years. Ten out of 12 SCIE mega-journals collected in this study show a high impact factor, which is above average. Furthermore, the number of articles published by South Korean authors in major mega-journals is also on the rise. The result of this study will be useful for mega-journal editors, who are keen to know what factors influence author choice of journals, and for those who attempt to predict what impact mega-journals will have on scholarly journal publishing in the future.